Longitudinal monitoring of T cell dynamics in metastatic breast cancer via a remote diagnostic implant - Ian A. Schrack; Rebecca S. Pereles; Brian C. Ross; Jeffrey A. Ma; Russell R. Urie; Emily R. Irish; Guillermo Escalona; Kate V. Griffin; Kathryn Kang; Jacqueline S. Jeruss; Lonnie D. Shea Ph.D. (ImmunoMedicine)
Abstract Metastatic triple negative breast cancer poses a significant health challenge due to rapid progression and limited treatment options. Immunotherapies targeting T cell responses against metastatic tumors depend on the presence of specific T cell phenotypes, which dynamically evolve with disease progression and treatment. Herein, we investigate T cell phenotype dynamics throughout metastatic disease progression, focusing on both the metastatic site in the lung and a biomaterial implant that serves as a synthetic metastatic niche, with the latter providing an accessible, non‐vital tissue for longitudinal analysis. Regulatory T cells were reduced at the lung and scaffold implant sites of metastasis following disease onset and progression relative to healthy mice, while Th1 and Th17 populations remained relatively stable. CD8+ T cells transitioned from naïve and central memory to effector memory with disease progression. Additionally, functional analyses involving the metastatic tissues suggested the primary T cell suppressive mechanism was reduced migration, with no impact on T cell activation. Blood‐based analyses demonstrated some of these phenotypic dynamics yet do not recapitulate the functional assays. Collectively, the scaffold provides a platform for dynamically monitoring T cell phenotypes and functions similar to the metastatic lung, enabling longitudinal monitoring of disease progression that could stratify patient populations.